Rewired glutamate metabolism diminishes cytostatic action of L-asparaginase - Hlozkova, Katerina; Vasylkivska, Maryna; Boufersaoui, Adam; Marzullo, Bryan; Kolarik, Matus; Alquezar-Artieda, Natividad; Shaikh, Mehak; Alaei, Nadia Fatemeh; Zaliova, Marketa; Zwyrtkova, Martina; Bakardijeva-Mihaylova, Violeta; Alberich-Jorda, Meritxell; et al. (Cancer letters, 2024)
Tumor cells often adapt to amino acid deprivation through metabolic rewiring, compensating for the loss with alternative amino acids/substrates. We have described such a scenario in leukemic cells treated with L-asparaginase (ASNase). Clinical effect of ASNase is based on nutrient stress achieved by its dual enzymatic action which leads to depletion of asparagine and glutamine and is accompanied with elevated aspartate and glutamate concentrations in serum of acute lymphoblastic leukemia patients. We showed that in these limited conditions glutamate uptake compensates for the loss of glutamine availability. Extracellular glutamate flux detection confirms its integration into the TCA cycle and its participation in nucleotide and glutathione synthesis. Importantly, it is glutamate-driven de novo synthesis of glutathione which is the essential metabolic pathway necessary for glutamate's pro-survival effect. In vivo findings support this effect by showing that inhibition of glutamate transporters enhances the therapeutic effect of ASNase. In summary, ASNase induces elevated extracellular glutamate levels under nutrient stress, which leads to a rewiring of intracellular glutamate metabolism and has a negative impact on ASNase treatment.
Keywords: Citric Acid Cycle; nádorové buněčné linie; Xenograft Model Antitumor Assays; asparaginasa; Glutathione; akutní lymfatická leukemie; Asparaginase; Mice; Glutamine; Cell Line, Tumor; Antineoplastic Agents; xenogenní modely - testy protinádorové aktivity; protinádorové látky; zvířata; Humans; glutathion; myši; Glutamic Acid; kyselina glutamová; glutamin; citrátový cyklus; Precursor Cell Lymphoblastic Leukemia-Lymphoma; lidé; Animals